Adhesive and antibacterial films based on marine-derived fucoidan and chitosan - Correia, C. (2022)
Marine-derived polymers are environmentally friendly and sustainable biomaterials that have structural similarities with the main components of the extracellular matrix. Moreover, some marine polymers have specific bioactivity that can be transferred to the systems made of these biomolecules. Herein, we developed antibacterial adhesive films combining two marine polysaccharides, namely, fucoidan and chitosan. Fucoidan was functionalized with catechol groups (FCat) to improve its adhesive properties. This modification enhanced also the fucoidan antibacterial properties: while fucoidan is active against Gram-positive bacteria, FCat showed bactericidal activity against Gram-positive and Gram-negative bacteria. To improve the processability and mechanical properties, FCat was blended with chitosan and solvent-casted to obtain films. These films exhibited an adhesion strength similar to the one of clinically used natural adhesives and no cytotoxicity: fibroblastic cells attached and remained viable on the films. Altogether our results demonstrated that the developed antibacterial and adhesive films are a feasible alternative of cytotoxic synthetic adhesives used for soft tissue healing applications.